Зарубежный опыт страхования инвестиций (Путеводитель предпринимателя)
The foreign practical experience of investment insurance is analyzed in the article. The main insurance conditions of participation of OPIC, MIGA and Euler Hermes Kreditversicherungs-AG are also considered in this investigation.